Establishment of Highest Bureaucratic Elite in Russian Empire in 19th— Early 20th Centuries: Education and Professional Qualifications - D. I. Raskin (Научный диалог)
The issue of the role of education and professional qualifications in the establishment of the highest bureaucratic elite in the Russian Empire in the 19th — early 20th centuries is considered in the article. Particular attention is paid to the availability of special (profile) education for ministers and department directors of the main civilian departments. The connection between the attempt to differentiate the requirements for the educational qualification of officials de-pending on the type of service at the beginning of the 19th century, on the one hand, and projects to abolish civil ranks, on the other are analyzed. The results of a comparative analysis of information about education and service experience of representatives of the highest bureaucracy of various departments are presented. Special attention is paid to medical and “technical” departments, the leadership of which required special qualifications.  It is shown that legal education has come to be considered a profile qualification not only for the judicial, but also for the administrative service. The age characteristics of Russian ministers at the time of their occupation of ministerial posts are given. It has been proved that the problem of raising the educational level of the Russian bureaucracy was largely solved for the upper and middle level of the Russian bureaucracy by the end of the 19th and the beginning of the 20th centuries, but the problem of professional qualifications still existed, although significant steps were taken to resolve it.